A Brief Overview of History, Pathogenesis and Treatment of Perforated Peptic Ulcer Disease with Evaluation of Prognostic Scoring in Adults - V. Prabhu; A. Shivani (Highlights on Medicine and Medical Research Vol. 9, 2021)
Peptic ulcer disease, which includes both gastric and duodenal ulcers, accounts for a substantial part of patients seeking surgical assistance worldwide. The discovery of H2-receptor antagonists revolutionised the idea of acid in peptic ulcer disease, which contributed to the theory of acid suppression therapy for duodenal ulcer, which followed decades of preference for surgical treatments such as gastric resections, vagotomy, and other procedures. Following the identification of the Helicobacter pylori organism as the causative factor, a triple drug treatment regimen for peptic disease was described, which was later changed to concurrent therapy to prevent antibiotic resistance. The chapter on peptic ulcers has not yet come to an end as a result of this recognition. Ulcer disease and its complications continue to be a surgical challenge. All the materials for this review have been accessed from various internet search engines. The references have been narrowed down to 34 by excluding cross references, duplicated citations, pediatric studies, case reports, iatrogenic and malignant perforations and including microbiological, immunohistochemistry references and studies with more than a sample size of ten. Case control, cohort studies, prospective/retrospective, metaanalytical studies were preferred in that order. This article attempts to take an overview of all aspects of the management of peptic ulcer. In proved cases of gastro duodenal ulcers on endoscopy use of triple drug therapy for elimination of H. pylori is mandatory.